Inhibition of biogenic hydrogen sulfide produce by Sulfate Reducing Bacteria isolated from oil fields in Basra by nitrate based treatment - Al-Tamimi , Wijdan H.; Mehdi, Kawther H. (Journal of Petroleum Research and Studies, 2017)
The present study included using of Bio Competitive Exclusion BCX technology in treatment of biogenic production of hydrogen sulfide H2S by Sulfate Reducing Bacteria SRB in batch cultures, injection of nitrate and nitrite promotes the growth of Nitrate Reducing Bacteria NRB which outcompete the Sulfate Reducing Bacteria SRB on carbon sources. Mix cultures of SRB and NRB were isolated from produce water of oil production facilities in Iraq including Nahran Omer and Al lahis oil fields. The activity of NRB and SRB were determined by measured the concentration of nitrate, nitrite and sulfide by using spectrophotometer and bacterial counts in three tube MPN technique. The results showed that NRB had a certain inhibitory effect on the growth of SRB and sulfide production under adding NRB nutrient nitrate and nitrite at all concentrations 200, 400, 600, 800 and 1000 mg/l, activity of NRB increased after treatment, all nitrate and nitrite consumption during 2 - 3 days of incubation. The highest inhibition of H2S production was at concentration 1000 mg/l of nitrate where the results showed that there was significant decrease in sulfide level and number of bacteria 34 mg/l and 34.8 cell/ ml respectively after 10 days of treatment.